18F-FDG PET for detecting recurrent head and neck cancer, local lymph node involvement and distant metastases - Schmidt, M.; Schmalenbach, M.; Jungehülsing, M.; Theissen, P.; Dietlein, M.; Schröder, U.; Eschner, W.; Stennert, E.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: Assessment of the clinical value of 18F-FDG-PET for detection of recurrent head and neck cancer, local lymph node involvement and distant metastases comparing a qualitative visual with a semiquantitative analysis (SUV values). Patients, methods: Retrospective evaluation of 73 18F-FDG PET studies in 55 patients by use of a four-step qualitative visual grading system and calculation of standard uptake values in pathological lesions. Calculation of SUV values in normal regions for generating a map of physiological 18F-FDG distribution. Correlation to histopathological findings and clinical follow-up. Results: 1. Qualitative visual analysis of 18F-FDG PET studies: a) local recurrence sensitivity 79%, specificity 97%, positive predictive value 95%, negative predictive value 85%, and diagnostic accuracy 89%; b) local metastatic lymph nodes 100%, 95%, 85%, 100%, 96%; c) distant metastases 100%, 98%, 86%, 100%, 98%, respectively. 2. Semiquantitative analysis had only little incremental, non-significant value in comparison to qualitative visual analysis for the detection of a local recurrence in two patients: a) local recurrence: sensitivity 83%, specificity 100%, positive predictive value 100%, negative predictive value 88%, and diagnostic accuracy 93%; b) local metastatic lymph nodes or c) distant metastases did not change in comparison to qualitative visual analysis. Conclusion:18F-FDG PET is an effective tool for re-staging of patients with suspected recurrence after therapy for head and neck cancer.
Keywords: 18F-FDG positron emission tomography; recurrent head and neck cancer; metastases; standard uptake value